Antiviral Activity of Isatis indigotica Extract and Its Derived Indirubin against Japanese Encephalitis Virus. (11th June 2012) - Chang, Shu-Jen; Chang, Yi-Chih; Lu, Kai-Zen; Tsou, Yi-Yun; Lin, Cheng-Wen
Abstract : Isatis indigotica is widely used in Chinese Traditional Medicine for clinical treatment of virus infection, tumor, and inflammation, yet its antiviral activities remain unclear. This study probed antiviral activity of I. indigotica extract and its marker compounds against Japanese encephalitis virus (JEV). I. indigotica methanol extract, indigo, and indirubin proved less cytotoxic than other components, showing inhibitory effect (concentration-dependent) on JEV replication in vitro . Time-of-addition experiments proved the extract, indigo, and indirubin with potent antiviral effect by pretreatment (before infection) or simultaneous treatment (during infection), but not posttreatment (after entry). Antiviral action of these agents showed correlation with blocking virus attachment and exhibited potent virucidal activity. In particular, indirubin had strong protective ability in a mouse model with lethal JEV challenge. The study could yield anti-JEV agents.